Comparison of pain threshold, health and disability status of female patients with fibromyalgia and multiple sclerosis - Ozgocmen, S; Kaya, A; Gulkesen, A; Bulut, S; Ardicoglu, O (B M J Publishing Group, 2004)
[Abstract Not Available]
Annual European Congress of Rheumatology (EULAR 2004) -- JUN 09-12, 2004 -- Berlin, GERMANY